Milestones in the History of Ear Reconstruction - Berghaus, Alexander; Nicoló, Marion San (Facial Plastic Surgery, 2015)
The reconstruction of ear deformities has been challenging plastic surgeons since centuries. However, it is only in the 19th century that reports on partial and total ear reconstruction start increasing. In the quest for an aesthetically pleasing and natural-looking result, surgeons worked on the perfect framework and skin coverage. Different materials and flap techniques have evolved. Some were abandoned out of frustration, while others kept evolving over the years. In this article, we discuss the milestones in ear reconstruction—from ancient times to early attempts in Western civilization to the key chapters of ear reconstruction in the 20th century leading to the current techniques.
Keywords: ear reconstruction; history of ear reconstruction; rib cartilage; porous polyethylene